Acinetobacter baumannii Biofilm Formation in Human Serum and Disruption by Gallium - Runci, Federica (Antimicrob Agents Chemother, 2016)
Biofilm-associated infections caused by Acinetobacter baumannii are extremely recalcitrant to antibiotic treatment. We report that A. baumannii develops a mature biofilm when grown in complement-free human serum (HS). We demonstrate that 16 μM gallium nitrate (GaN) drastically reduces A. baumannii growth and biofilm formation in HS, whereas 64 μM GaN causes massive disruption of preformed A. baumannii biofilm. These findings pave the way to the repurposing of GaN as an antibiofilm agent for A. baumannii.